Efektivitas Kegiatan Gerakan Literasi Sekolah dalam Meningkatkan Minat Literasi Siswa di SMPN 20 Medan - Alfany Umar; Abdul Karim Batubara (Prodi Pendidikan Sejarah Fakultas Keguruan dan Ilmu Pendidikan Universitas Islam Sumatera, 2023)
This research departs from the School Literacy Movement (GLS) programme launched by the Ministry of Education and Culture, as an effort to increase the literacy awareness of the nation's children. This research examines how the effectiveness of GLS activities in increasing students' interest in reading. This research uses a qualitative approach method with a descriptive type of research with the aim of explaining the effectiveness of the School Literacy Movement activities in increasing students' interest in literacy, the location is SMPN 20 Medan and data collection methods using an observation and interviews. The questions of research in this study are, what are the factors that influence the effectiveness of GLS activities at SMPN 20 Medan, how is the effectiveness of GLS activities in increasing students' interest in literacy at SMPN 20 Medan? This study concludes that there are internal and external factors that influence the effectiveness of GLS activities. In relation to the effectiveness of GLS in increasing students' interest in reading, this study concludes that GLS is quite effective in increasing students' interest in reading at SMPN 20 Medan. Finally, this study recommends SMPN 20 Medan to improve the quality of GLS activities by modernizing and digitalizing based information technology-activities.